New species of tarantulas from Brazil and notes on the Hapalopini tribe (Araneae, Theraphosidae, Theraphosinae) - Moeller, Wolf [UNESP] (2024)
The monophyly of Theraphosinae is supported by both morphological and molecular phylogenies. However, intergeneric relationships often show polytomies and branches with low support. A previous phylogenetic study proposed an intergeneric relationship for the subfamily based on molecular data and divided it into three tribes: Grammostolini, Hapalopini and Theraphosini. However, not all genera of Theraphosinae were sampled, and some relationships were inferred based on morphological similarities. Regarding the Hapalopini from Brazil, the relationships of some genera are still uncertain, such as Kochiana, Catanduba, and Munduruku. In this paper, we describe four new species of Hapalopini from Brazil: Cyriocosmus paresi sp. nov., Hapalopus akroa sp. nov., H. guidonae sp. nov., and K. fukushimae sp. nov. In addition, we propose an updated diagnosis for these three genera and for the species K. brunnipes and M. bicoloratum.